Atividade enzimática, cinética e modelagem matemática da decomposição de Ultricularia breviscapa da lagoa do Óleo (Estação Ecológica de Jataí, Luiz Antônio - SP) - Santino, Marcela Bianchessi da Cunha (Universidade Federal de São Carlos, 2003)
This work approached the enzymatic activities, kinetics and mathematical modeling of the decomposition of Utricularia breviscapa from ºleo lagoon (21° 36' S and 47° 49' W), Luiz Antonio, SP. The experiments described the decomposition in function of temperature, availability of oxygen and carbon source. Samples of this macrophyte and water were collected in the oleo lagoon; incubations were prepared and maintained in controlled conditions. The results allow us to conclude that: (i) the U. breviscapa detritus are a heterogeneous substrata and presented two fractions: a labile/soluble (COPLS » 23.5%) and a refractory (COPR » 76.5%). The mass losses coefficients of the labile/soluble fractions (kT = 1.5 day-1) were higher than the refractory fractions (309 times in the aerobic condition and 469 times in the anaerobic condition). The increasing temperature and the dissolved oxygen concentrations favored the mineralization of the refractory fractions. The COPR mineralization in the aerobic conditions was faster than in the anaerobic conditions (1.5 times); (ii) the enzymatic activities of the cellulase presented a temporal pattern that was affected by the temperature, availability of oxygen and carbon source; (iii) stoichiometric ratio (O/C) varied in function of temperature and time; (iv) the oxygen uptake coefficients (kd) presented low variation in function of increasing temperature; (v) the increment on temperature favored the CH4 formation in the anaerobic decomposition of U. breviscapa and its emissions tended to occur earlier; (vi) probably, the enzymatic degradation of the cellulose in the anaerobic strata of sediments contributed to methanogenesis in the oleo lagoon; (vii) the simulations indicated that heterotrophic potentials of the oleo lagoon presents low variations during the year; the favorable period for detritus cycling is in the spring (October - November), in this period increments in mineralization occurs as function of increasing temperature and high availability of oxygen.
Keywords: Ecologia aquática; Consumo de oxigênio; Celulose; Metano; Modelos matemáticos; Macrófitas aquáticas; CIENCIAS BIOLOGICAS::ECOLOGIA